Reservoir Characterization Using Post Stack Seismic Inversion on The Upper Sihapas Formation, Malacca Strait, Central Sumatra Basin - Candra Teja Kusuma; Md. Shofiqul Islam; Sadiq Jalal; Thais de Souza Kazmierczak; Luis Antonio Castillo-López (Frontier Advances in Applied Science and Engineering, 2024)
Post-stack seismic inversion is often conducted to quantitatively determine the characteristics of reservoirs using post-stack seismic data, with the output being acoustic impedance. Rock characteristics such as porosity, lithology, and fluids can be represented by impedance values, making the distribution of impedance the focus of this study in determining potential areas of interest. The research area is located in the Malacca Strait Block, Central Sumatra Basin, with the reservoir in the Upper Sihapas Formation. This study uses post-stack seismic inversion with acoustic impedance values ​​as the output. With a crossplot of acoustic impedance vs. porosity and the color from the gamma ray log, sand and shale lithologies can be separated. The crossplot also produces a simple linear equation to convert acoustic impedance values ​​to porosity values. The reservoir zone has acoustic impedance values ranging from 13,000 (ft/s)*(g/cc) to 16,500 (ft/s)*(g/cc), which are converted into porosity values ranging from 9% to 40% . Point bars, crevasse splays, and restricted brackish bays are areas with good reservoir quality, as indicated by low acoustic impedance values.